Associations of Blood Cadmium Levels With Osteoarthritis Among US Adults in NHANES 2013-2018 - Li, Lijun; Cao, Jiangang; Li, Lin; Wu, Guang; Xiao, Junhui (Journal of occupational and environmental medicine, 2024)
Osteoarthritis (OA) is a global public health problem, and limited information is available on the effects of Cd on OA. The purpose of this study is to explore the relationship between Cd and OA. Weighted multivariable logistic regression model, trend test, restricted cubic spline, and stratified analysis were used to study the association between BCd and OA. In the two regression models of weighted multivariable logistic regression analysis, the correlation between BCd and OA was positive. Compared with the lowest quartile of BCd exposure, the highest quartile had a 2.03-fold (95% confidence interval, 1.67 to 2.47), displaying a dose-response relationship (P for trend <0.00001). The restrictive cubic spline shows a positive linear relationship between BCd and OA. There was a positive linear relationship between BCd and OA and a dose-response relationship.